1983
DOI: 10.1128/jb.154.1.200-210.1983
|View full text |Cite
|
Sign up to set email alerts
|

Transport of hemolysin across the outer membrane of Escherichia coli requires two functions

Abstract: MATERIALS AND METHODS Bacterial strains. E. coli K-12(pHlyl52) and the Tn3 mutants of pHlyl52 have been described previously (20, 21). E. coli 605 carrying TnS in the chromosome was given to us by A. Piihler. Plasmids. The recombinant plasmid pANN202-312, carrying the whole hly determinant of pHlyl52, and its derivatives have been recently described (8). The vector plasmid pUR222 was a gift from B. Muller Hill. Cleavage with restriction enzymes and in vitro recombination. Restriction enzyme cleavage, in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(100 citation statements)
references
References 29 publications
3
95
1
1
Order By: Relevance
“…1 we present a complete summation of the biology of the E. coli hemolysin. The four hly genes and their respective proteins were first identified through the efforts of the Goebel laboratory in Wurzburg and our laboratory [13][14][15][16]. Recently, Wandersman's laboratory has shown that TolC is necessary for export of the hemolysin [17].…”
Section: Geneticsmentioning
confidence: 99%
“…1 we present a complete summation of the biology of the E. coli hemolysin. The four hly genes and their respective proteins were first identified through the efforts of the Goebel laboratory in Wurzburg and our laboratory [13][14][15][16]. Recently, Wandersman's laboratory has shown that TolC is necessary for export of the hemolysin [17].…”
Section: Geneticsmentioning
confidence: 99%
“…Distinct from this is the so-called type I export process, whereby translocation of protein toxins, proteases and nodulation factors across both membranes is achieved directly, in an 'all-or-nothing' fashion without a periplasmic intermediate Guzzo et al, 1990;Glaser et al, 1988;Letoffe et al, 1990;Rivilla et al, 1995;Koronakis et al, 1989;Koronakis and Hughes, 1993); the substrate either crosses both membranes or remains in the cytoplasm. This process requires an inner-membrane translocator, comprising an ABC exporter and an accessory protein speculated to act in a bridging role (Wagner et al, 1983;Dinh et al, 1994), and the outer membrane protein TolC , which has been reported to be able to form ion-permeable channels (Benz et al, 1993). Homologues of these components are also responsible for the efflux of small toxic compounds, including antibiotics (Nagel de Zwaig and Luria, 1967;Davies and Reeves, 1975;Nikaido, 1994;Li et al, 1995;Ma et al, 1994;Poole et al, 1993;Fralick, 1996), and are required for invasive virulence (Stone and Miller, 1995), emphasizing the medical importance of this export mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…At present three independent secretion systems have been iden-ti¢ed and characterized in these bacteria. The Escherichia coli hemolysin (HlyA) secretion apparatus is a prototype of the type I secretion system consisting of two cytoplasmic membrane proteins HlyB and HlyD and the outer membrane protein TolC [2,3]. The Hly secretion apparatus recognizes a signal sequence (HlyA s ), located at the C-terminus of hemolysin (HlyA), that comprises the last 46 [4] to 62 amino acids of HlyA [5].…”
Section: Introductionmentioning
confidence: 99%